Compressive behavior and energy absorption capacity of unconstrained and constrained open-cell aluminum foams. (4th May 2020) - Li, Chengbing; Li, Chunxing; Wang, Yazhou
In practical engineering applications, while the open-cell aluminum foam as crash absorber is filled to the hollow structures, its deformation occurs under constrained stress boundaries. The experimental work was conducted to examine the effect of radial constraints on the mechanical behavior of the open-cell aluminum foam under quasi-static and dynamic compression. Results show that the radial constraints induce significant strain hardening of the open-cell aluminum foam. The open-cell aluminum foams tested with and without radial constraints show a clear strain rate sensitivity. The densification of the foam occurs earlier (showing lower densification strain) under radial constraints. The radial constraints enhance the energy absorbed per unit volume of the open-cell aluminum foam.